Development and External Validation of a Nomogram for Predicting Cancer-Specific Survival of Non-Small Cell Lung Cancer Patients With Ipsilateral Pleural Dissemination - Wang, Zhenfan; Li, Hao; Liu, Taorui; Sun, Zewen; Yang, Fan; Jiang, Guanchao (Frontiers in Oncology, 2021)
Background: Non-small-cell lung cancer (NSCLC) patients with ipsilateral pleural dissemination are defined as M1a in the eighth of American Joint Committee on Cancer (AJCC) TNM staging. We aimed to build a nomogram to predict lung cancer specific survival (LCSS) of NSCLC patients with ipsilateral pleural dissemination, and to compare the impact of primary tumor resection (PTR) on LCSS among patients with different feature. Methods: A total of 3918 NSCLC patients with ipsilateral pleural dissemination were identified from the Surveillance, Epidemiology, and End Results (SEER) database. We selected and integrated significant prognostic factors based on competing risk regression to build a nomogram. The model was subjected to internal validation within SEER cohort and external validation with the cohort of 97 patients from Peking University People’s Hospital. Results: Age (P<0.001), gender (P=0.037), T stage (P=0.002), N stage (P<0.001), metastasis pattern (P=0.005), chemotherapy (P<0.001) and PTR (P<0.001) were independent prognostic factors. The calibration curves presented a good consistency and the Harrell's C-index of nomogram were 0.682 (95%CI: 0.673-0.691), 0.687 (95%CI: 0.670-0.704) and 0.667 (95%CI: 0.584-0.750) in training, internal and external validation cohort, respectively. Interaction tests suggested a greater LCSS difference caused by PTR in patients without chemotherapy (P<0.001). Conclusions: We developed a nomogram based on competing risk regression to reliably predict prognosis of NSCLC patients with ipsilateral pleural dissemination, and validated this nomogram in an external Chinese cohort. This novel nomogram might be a practical tool for clinicians to anticipate the 1-, 3- and 5-year LCSS for NSCLC patients with pleural dissemination. Subgroup analysis indicated that patients without chemotherapy could get more benefit from PTR. In order to assess the role of PTR in the management of M1a patients more accurately, further prospective study would be urgently required.